UJI POTENSI ANTIKANKER PAYUDARA PADA EKSTRAK MENIRAN (Phyllanthus niruri L.) SECARA IN VITRO TERHADAP SEL LINE MCF-7 - Margita Savitri; apt. Ernie Halimatushadyah, M.Farm; apt. Krismayadi, S.Si., M.M., M.farm (LPPM Universitas Cipta Mandiri, 2024)
Cancer is the second leading cause of death worldwide, the most common cancer cases are breast cancer. Breast cancer occurs when breast cell growth is uncontrolled due to genetic changes that are not involved in regulating cell growth. Meniran (Phyllanthus niruri L.) It contains flavonoids and tannins that can be used as anticancer agents. This study aims to determine the potential of meniran extract (Phyllanthus niruri L.) as an anticancer breast against MCF-7 cell line and knowing the IC50 value of meniran extract (Phyllanthus niruri L.) against MCF-7 cell lines. The research method used is experimental by conducting an MTT Assay test. The extraction method used in this study was maceration using 70% ethanol solvent. The positive control used is doxorubicin. Meniran extract (Phyllanthus niruri L.) in this study it can be said to be not potential with an IC50 value of 510.98 ppm while in doxorubicin IC50 obtained of 4310.53 ppm